Phenotypic and genotypic characterisation of mycobacterium tuberculosi strains in relation to the transmission of tuberculosis in South African mines - Muthivhi., Tshilidzi, Neleus. (My University, 2000)
The prevalence of tuberculosis in South African miners is substantially higher than that of in the general population. Through exposure to dust which leads to different degrees of silicosis, and by working in enclosed spaces where coughed out bacilli can survive in droplet nuclei and be inhaled by other workers, miners are especially prone to to become infected with M. tuberculosis and develop the disease. It is not only the working conditions which promote transmission of M. tuberculosis, but the living conditions as well. Most miners live and sleep in rooms shared by up to eight other men, which increases the opportunity for transmission, leading to both primary and reinfection tuberculosis.
A thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy.
Keywords: Mycobacterium tuberculosis; Silicosis; Bacillus